A territorialização dos conhecimentos tradicionais sobre plantas medicinais: a experiência do coletivo de mulheres agricultoras do Sintraf-FB - Schmitz , Aline Motter (2023)
Traditional knowledge about medicinal plants, ranging from their cultivation, identification and use, is maintained and transmitted by women farmers between generations, but also taken to the agenda of women's organizations. Therefore, we aim to analyze the territorialization of traditional knowledge about medicinal plants in the city of Francisco Beltrão, based on the experience of use, cultivation and commercialization of medicinal plants, through the actions of women farmers who are part of the Collective of Women Farmers of the Family Farming Workers Union of Francisco Beltrão – Sintraf-FB. The Collective studied was structured in 2009, as a result of a historical process of the political organization of the women farmers of the city and under the influence of an extension project of the State University of Western Paraná (Universidade Estadual do Oeste do Paraná) – Unioeste. Among its agendas are the appreciation and rescue of traditional knowledge related to medicinal plants, which evolve into an alternative income for women farmers through the sale of natural plants for school lunches in the city of Francisco Beltrão, by the National Food Program School – Pnae. However, the intersectionality between the patriarchal order of gender, capitalism and coloniality in Family Farming imposes difficulties on women in their organization in public spaces. In this way, the collective organization of the association is not consolidated and most women farmers give up the commercialization of medicinal plants. The ones who continue to sell medicinal plants do so individually, linked to the Central Cooperative of Integrated Family Agriculture of Paraná – Coopafi. In this context, the Collective’s organization itself dismantles, due to numerous problems related to the organization of the Association of Women Producers of Herbs and Medicinal Products of Francisco Beltrão – Ampema, but also due to the loss of leadership and organization of these women by Sintraf-FB. This research is qualitative, carried out through bibliographical analysis and the collection of primary and secondary information, consulting files and people from Sintraf-FB, Coopafi, the city hall of Francisco Beltrão and Unioeste.